Extending the scale of obsidian studies: Towards a high‐resolution investigation of obsidian prehistoric circulation patterns in the southern Caucasus and north‐western Iran. (15th March 2021) - Orange, M.; Le Bourdonnec, F.‐X.; Berthon, R.; Mouralis, D.; Gratuze, B.; Thomalsky, J.; Abedi, A.; Marro, C.
Abstract : Recent archaeological research has highlighted the potential role of mobile pastoral groups in the diffusion of raw materials and technological innovations between the southern Caucasus and north‐western Iran from the Neolithic onwards. Two successive projects, PAST‐OBS and SCOPE, were designed to explore this hypothesis through the study of obsidian consumption patterns from the Neolithic to the Bronze Age using a flexible analytical strategy that considerably extends the scale of obsidian studies in these regions. By focusing on the exploitation of obsidian at multiple levels—local, regional and interregional—we hope to unravel the complexity of the obsidian networks under study. The aim of this paper is to present (1) a reassessment of the work so far carried out by previous obsidian studies, with a view to homogenizing and to clarifying the nomenclature in use; and (2) an introduction to the PAST‐OBS and SCOPE projects in order to initiate a discussion of our preliminary results.